AB1166 The association of the early onset of remitting seronegative symmetrical synovitis with pitting oedema (RS3PE) syndrome with dipeptidyl peptidase-4 (DPP4) inhibitor. (12th June 2018) - Yoshioka, Y.; Mitsuhashi, M.; Kato, A.; Kanai, D.; Suda, A.; Nagaoka, S.
Abstract : Background: Remitting seronegative symmetrical synovitis with pitting oedema (RS3PE) syndrome is a rare inflammatory arthritis, characterised by absence of rheumatoid factor, symmetrical distal synovitis, pitting oedema of the hands and feet. In recent years the use of dipeptidyl peptidase-4 (DPP4) inhibitor has increased and some reports have described the association of RS3PE syndrome with DPP4 inhibitor. Objectives: We have tried to investigate the association of RS3PE syndrome with DPP4 inhibitor in our hospital. Methods: In Japan DPP4 inhibitor was released in December 2009, so we retrospectively analysed background, treatment and clinical course of 25 patients with RS3PE syndrome diagnosed between December 2009 and December 2016 in our hospital. We divided them in two groups according to DPP4 inhibitor prescription and compared two groups. Results: Our cases included 18 males and 7 females, and the mean age of RS3PE syndrome onset was 76 years old. The mean follow-up period was 32.5 months. Six patients had diabetes mellitus and DPP4 inhibitor was prescribed in five of six patients (83.3%). (sitagliptin 3 cases, teneligliptin 1 case, alogliptin 1case). The duration of RS3PE syndrome onset after DPP4 inhibitor prescription was mean 22.9 months, and two cases developed within a half year, two cases after two years. Compared with non DPP4 inhibitor group, the mean age of RS3PE syndrome onset was significantly low (70 vs 78.5, p=0.023), and HbA1c (NGSP) was high (7.3% vs 6.02%, p=0.00022) in DPP4 inhibitor group. The occurrence of flare was four cases in non DPP4 inhibitor group and zero in DPP4 inhibitor group, but was not statistically different (p=0.275). Other clinical features were not significantly different. Conclusions: DPP4 inhibitor group was significantly younger than non DPP4 inhibitor group, and the possibility that DPP4 inhibitor contributed to the early onset of RS3PE syndrome was suggested. References: [1] Oyama K, Taniguchi J, et al. Remitting seronegative symmetrical synovitis with pitting edema syndrome in individuals with type 2 diabetes mellitus or impaired glucose tolerance. Diabetes Res Clin Pract. 2015Oct;110(1):e5–8. [2] McCarty DJ, O'Duffy JD, et al. Remitting Seronegative Symmetrical Synovitis with Pitting Edema (RS3PE Syndrome). JAMA 1985; 254: 2763–2767. Disclosure of Interest: None declared